The effect of sleep quality on learning engagement of junior high school students: the moderating role of mental health - Xu, Zhenguo; Niu, Menghui; Du, Wenxiu; Dang, Tongtong (Frontiers in Psychology, 2025)
IntroductionA good quality of sleep is not only an important guarantee for students’ academic life, but also an important founding condition for their physical and mental health development. The study aims to explore the relationship between sleep quality and students’ learning engagement, and to deeply analyze the moderating role played by mental health.MethodsA questionnaire survey was conducted among some junior high school students in Rizhao City, Shandong Province for the research.ResultsThe results show that: (1) The main effect of sleep quality on learning engagement is significant (β = 0.476, t = 1.829, p < 0.001), specifically, the better the sleep quality, the higher the students’ learning engagement. (2) The influence of sleep quality on learning engagement is moderated by mental health (β = –0.850, t = -2.652, p = 0.006), that is to say, the influence of sleep quality on learning engagement is more significant for students with poor mental health, and mentally healthy students can effectively alleviate the negative impact of sleep problems on their learning engagement.DiscussionResearch shows the significance of good sleep quality and mental health for students’ learning. The research results provide empirical evidence for schools, families, and policy makers to improve students’ academic achievement and mental health.